Platinum-group-metal catalysts for proton exchange membrane fuel cells: From catalyst design to electrode structure optimization. Issue 1 (January 2020) - Hou, Junbo; Yang, Min; Ke, Changchun; Wei, Guanghua; Priest, Cameron; Qiao, Zhi; Wu, Gang; Zhang, Junliang
Highlights: This review provided a comprehensive understanding on fuel cell electrocatalysis in terms of cathode catalysts and electrode design. State of the art Pt based catalysts, carbon supports, proton conductive ionomers, and their structure effects are reviewed. Important factors of Pt catalyst design are identified with rational understanding. The catalyst layer structures are discussed to provide insight into the optimization of the critical three-phase interfaces. Electrochemistry of the Pt/ionomer interface, as well as interfacial water and sulfonate poisoning are summarized. Graphical abstract: Image, graphical abstract Abstract: Proton exchange membrane fuel cells (PEMFCs) have attracted significant attention in the past three decades as a very promising power source for transportation applications. After tremendous efforts worldwide, fuel cell vehicles are now being pushed to the market. At the early stage of fuel cell vehicle pre-commercialization, however, the performance, cost, and durability of PEM fuel cells are still in the process of improvement. Understanding fundamentals of fuel cell electrocatalysis provides new insight into the choice and design of fuel cell materials and components with higher performance and durability. State of the art Pt based catalysts, carbon supports, proton conductive ionomers, and their structure effects are discussed in this review. The primary effort is made on the catalysts to increase oxygen reduction reaction (ORR) activity and durability by using low platinum-group metal (PGM) catalysts. The size effect and a variety of nanostructures ( e.g., core-shell, Pt skin, dealloyed, monolayer, polyhedron facets, ligand, and strain effects) are comprehensively discussed to design and synthesize PGM catalysts for the cathode in PEMFCs. Using ionomer as the binder and proton conductors in the catalyst layer, the catalyst layer structure, ink preparation and deposition techniques, and ink drying process are also discussed. Due to the additional local transport resistance observed in fuel cell performance, the morphology and confinement effect of the ionomer thin film are also taken into account. In addition, the electrochemistry of the Pt/ionomer interface, as well as interfacial water and sulfonate poisoning are summarized.